2018
DOI: 10.3892/ijmm.2018.3648
|View full text |Cite|
|
Sign up to set email alerts
|

Connexin 43 reduces susceptibility to sympathetic atrial fibrillation

Abstract: Atrial fibrillation (AF) is the most common arrhythmia reported in clinical practice. Connexin 43 (Cx43) is a member of the connexin protein family, which serves important roles in signal transduction in vivo. The aim of the present study was to investigate the role of Cx43 in the induction and maintenance of atrial fibrillation by using an animal model of sympathomimetic atrial fibrillation. Cx43 was successfully knocked down in the myocardium with gene‑specific small interfering (si)RNA via lentiviral infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…In contrast, Alesutan et al demonstrated inhibition of Cx43 by AMPK (Alesutan et al, 2015); thus Cx43 and its interaction with AMPK in the context of electrical remodeling remains inconclusive. Furthermore, downregulation of Cx43 would lead to reduced EP coupling between atrial myocytes, which in turn would slow conduction velocity and increase AF susceptibility in atrial tissue (Luo et al, 2018). While we did not demonstrate a change in conduction velocity between groups there was a trend towards conduction lengthening in the vehicle treatment group.…”
Section: Stcontrasting
confidence: 62%
“…In contrast, Alesutan et al demonstrated inhibition of Cx43 by AMPK (Alesutan et al, 2015); thus Cx43 and its interaction with AMPK in the context of electrical remodeling remains inconclusive. Furthermore, downregulation of Cx43 would lead to reduced EP coupling between atrial myocytes, which in turn would slow conduction velocity and increase AF susceptibility in atrial tissue (Luo et al, 2018). While we did not demonstrate a change in conduction velocity between groups there was a trend towards conduction lengthening in the vehicle treatment group.…”
Section: Stcontrasting
confidence: 62%
“…In the process of myocardial ischemia or myocardial injury and fibrosis, the expression of Cx43 will decrease, resulting in electrophysiological remodeling of cardiomyocytes at the molecular level, leading to arrhythmia [ 25 , 26 ]. Moreover, the study has revealed that Cx43 reduces susceptibility to sympathetic atrial fibrillation [ 27 ]. In this study, it was found that after overexpression of SHP-1, the expression of Cx43 was significantly increased, indicating that SHP-1 can reduce myocardial fibrosis and effectively protect myocardial function.…”
Section: Discussionmentioning
confidence: 99%
“…In a sheep coronary infarct model, Cx43 was redistributed from the intercalated discs to the lateral surface, increasing fibroblast-cardiomyocyte coupling and resulting in an increased associated AF risk, likely due to impaired signal transduction between myocytes [134,135]. Another study showed Cx43 mediates the induction and maintenance of AF in a canine model [136]. Connexins can be regulated through phosphorylation by multiple kinases like CaMKII, PKA or PKC [137][138][139].…”
Section: Oxidative Stress and Inflammationmentioning
confidence: 99%